Peran Dinas Kesehatan Bojonegoro dalam Pengawasan Izin Praktik Tenaga Teknis Kefarmasian di Apotek - Ummah, Rohmatul; Alamanda, Asri Elies (Universitas Batanghari Jambi, 2024)
This study aims to determine the role of the Bojonegoro Regency Health Office in Supervising the Pharmacy Technical Staff (TTK) Practice Permit at Pharmacies and the legal consequences received by Pharmacists as Pharmacy Manager Pharmacists (APA). This research is normative-empirical legal research (applied normative law), with a qualitative approach, combining a normative legal approach with the addition of various empirical elements. The data collection method used in this research is information obtained directly in the field in the form of interviews and document studies from various sources related to legal norms. The results showed that socialization, monitoring and guidance were gradually implemented by the Bojonegoro District Health Office if there were new rules and/or regulations from the government. There is a direct inspection to the field, but it is not optimal, because there are obstacles, namely the lack of Health Human Resources at the Health Office. The legal consequences received by pharmacists from violations of the governing laws and regulations include administrative sanctions, disciplinary sanctions, and criminal sanctions. The conclusion that can be drawn is that the Supervision of Utilization of TTK Practice Permits in Bojonegoro Regency in its implementation is still not optimal because the Bojonegoro Regency Health Office cannot carry out Supervision routinely due to the lack of Health Human Resources at the Bojonegoro Regency Health Office. As well as the legal consequences that can be received ranging from administrative, disciplinary, to criminal sanctions.